Measurement of polarization dependence of two-photon absorption coefficient in InP using extended Z-scan technique for thick materials. (8th February 2018) - Oishi, Masaki; Shinozaki, Tomohisa; Hara, Hikaru; Yamamoto, Kazunuki; Matsusue, Toshio; Bando, Hiroyuki
Abstract: The two-photon absorption coefficient β in InP has been measured in the wavelength range of 1640 to 1800 nm by the Z-scan technique in relatively thick materials. The values of β have been evaluated from the fit to the equation including the spatial and temporal profiles of the focused Gaussian beam. The polarization dependence of β has also been measured. The dependence has been expressed very well by the expression of β with the imaginary part of the third-order nonlinear susceptibility tensor χ (3) .